The Use of Duolingo in Enhancing Students' Vocabulary Mastery at SMA Negeri 3 Bangko Pusako During Pandemic Covid-19 - Erfiani Erfiani; Cut Raudhatul Miski (Indonesian Journal of Integrated English Language Teaching, 2022)
Abstract Based on the writer’s observation in teaching and learning process, the students’ frequently encounter obstacles to memorize the words, confuse the meaning of the words, and difficulty in pronunciation. To solve this problem, the writer used a media to improve the students’ mastery in vocabulary. The media was using Duolingo. The aim of this research was to find out any significant difference of students’ vocabulary mastery between students’ taught by using Duolingo and without using Duolingo at SMA Negeri 3 Bangko Pusako During Pandemic Covid-19. This research was a quantitative research by an quasi-experimental design. In this research, there were two classes as a sample, that classes were an experimental class and control class. The population of this research were tenth grade of SMA Negeri 3 Bangko Pusako was 156 students’ which were 30 students as sample of this study using purposive sampling technique. The result of the research showed that the students’ on vocabulary mastery in experimental class was very good category and in control class was good category. On the independents sample T-test, the significant value was 0.000 lower than alpha 0.05, which meant the alternative hypothesis (Ha) was accepted while null hypothesis (HO) was rejected. It means that, there was any significant difference of students’ vocabulary mastery between students’ taught by using Duolingo and without using Duolingo at SMA Negeri 3 Bangko Pusako.  Keywords: Vocabulary Mastery, Duolingo, Covid-19